The Model of Legal Contract Between Courier and Expedition Company in Pamekasan Regency - Aminullah, Aminullah; Hanafi, Hanafi (Faculty of Law Universitas Trunojoyo Madura, 2024)
The status of couriers as expedited employees often raises legal issues, especially regarding fulfilling their rights as workers in the context of labour law protection in Indonesia. These legal issues are then exacerbated by enacting the labour copyright law, which is detrimental to many workers. This study aims to determine the implementation of the work agreement between the expedition company and the courier. This research analyses the work contract model between couriers and expedition companies in Pamekasan Regency. This research uses empirical legal research methods conducted at several expedition companies in Pamekasan. The result of the research is that the expedition company chooses to be financially responsible in implementing the employment contract with the courier, where the model of employment contract applied by the expedition company to the courier is a certain time employment agreement (PKWT), which is renewed every year, so there are several things that the company can avoid including severance pay, employee leave, overtime pay, and health insurance facilities.